Comparison of the effects of inhalational anesthesia with desflurane and total intravenous anesthesia on cardiac biomarkers after aortic valve replacement - Kapoor, Poonam Malhotra (Ann Card Anaesth, 2015)
OBJECTIVE (S): The aim of this study was to compare the effects of using inhalational anesthesia with desflurane with that of a total intravenous (iv) anesthetic technique using midazolam-fentanyl-propofol on the release of cardiac biomarkers after aortic valve replacement (AVR) for aortic stenosis (AS). The specific objectives included (a) determination of the levels of ischemia-modified albumin (IMA) and cardiac troponin I (cTnI) as markers of myocardial injury, (b) effect on mortality, morbidity, duration of mechanical ventilation, length of Intensive Care Unit (ICU) and hospital stay, incidence of arrhythmias, pacing, cardioversion, urine output, and serum creatinine. METHODOLOGY AND DESIGN: Prospective randomized clinical study. SETTING: Operation room of a cardiac surgery center of a tertiary teaching hospital. PARTICIPANTS: Seventy-six patients in New York Heart Association classification II to III presenting electively for AVR for severe symptomatic AS. INTERVENTIONS: Patients included in the study were randomized into two groups and subjected to either a desflurane-fentanyl based technique or total IV anesthesia (TIVA). Blood samples were drawn at preordained intervals to determine the levels of IMA, cTnI, and serum creatinine. MEASUREMENTS AND MAIN RESULTS: The IMA and cTnI levels were not found to be significantly different between both the study groups. Patients in the desflurane group were found to had significantly lower ICU and hospital stays and duration of postoperative mechanical ventilation as compared to those in the TIVA group. There was no difference found in mean heart rate, urine output, serum creatinine, incidence of arrhythmias, need for cardioversion, and 30-day mortality between both groups. The patients in the TIVA group had higher mean arterial pressures on weaning off cardiopulmonary bypass as well as postoperatively in the ICU and recorded lower inotrope usage. CONCLUSION: The result of our study remains ambiguous regarding the overall protective effect of desflurane in patients undergoing AVR although some benefit in terms of shorter duration of postoperative mechanical ventilation, ICU and hospital stays, as well as cTnI, were seen. However, no difference in overall outcome could be clearly established between patients who received desflurane and those that were managed solely with IV anesthetic technique using propofol.